2019
DOI: 10.3233/jad-190644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefits of Antioxidative Supplement Twendee X for Mild Cognitive Impairment: A Multicenter, Randomized, Double-Blind, and Placebo-Controlled Prospective Interventional Study

Abstract: Oxidative stress is part of the entire pathological process that underlies the development of Alzheimer's disease (AD), including the mild cognitive impairment (MCI) stage. Twendee X (TwX) is a supplement containing a strong antioxidative mix of eight antioxidants, which has been shown to have a clinical and therapeutic benefit in AD model mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
0
30
0
2
Order By: Relevance
“…In a multicenter, randomized, double-blind and placebo-controlled prospective interventional study, TwX showed a significantly higher score of the mini-mental state examination at 6 months compared with the placebo, and also a significant improvement of the Hasegawa dementia scale-revised score from baseline at 6 months, suggesting that a strong antioxidative therapy might be a useful way to prevent the conversion of MCI to AD [111].…”
Section: Twendee Xmentioning
confidence: 98%
“…In a multicenter, randomized, double-blind and placebo-controlled prospective interventional study, TwX showed a significantly higher score of the mini-mental state examination at 6 months compared with the placebo, and also a significant improvement of the Hasegawa dementia scale-revised score from baseline at 6 months, suggesting that a strong antioxidative therapy might be a useful way to prevent the conversion of MCI to AD [111].…”
Section: Twendee Xmentioning
confidence: 98%
“…Thus, recent studies have examined whether an antioxidant supplement, Twendee X (TwX), exhibits beneficial effects in a mouse model of AD with CCH [72,73]. TwX contains the antioxidants coenzyme Q10, niacin amid, L-cystine, ascorbic acid, succinic acid, fumaric acid, L-glutamine, and riboflavin [72][73][74]. One study administered TwX by oral gavage to APP23 mice, which overexpress the human APP Swedish mutant gene, that were treated with ameroid constrictors on bilateral common carotid arteries to induce CCH development [72,73].…”
Section: Preclinical Findings Obtained By Twendee X Administrationmentioning
confidence: 99%
“…On the basis of the described preclinical findings, the authors conducted a randomized, double-blind, placebo-controlled clinical trial to examine the efficacy of TwX in patients with MCI [74]. They assessed cognitive function using the Mini-Mental State Examination and Hasegawa Dementia Scale-revised scores at baseline and six months and compared the placebo (n = 37) and TwX (n = 41) groups [74]. Results revealed that cognitive function was improved in patients in the TwX group compared to the placebo group following six months of intervention [74].…”
Section: Effects Of Twx On Patients With MCImentioning
confidence: 99%
See 2 more Smart Citations